AVOCADO SEEDS (Persea americana Mill.): FORMULATIONS OF ELIXIR VARIED BY SOLVENTS COMPOSITION - Septia Andini; Lusi Indriani; Erni Rustiani (Universitas Pakuan, 2020)
Kidney stones disease is asignificant health problem in the world and Indonesia is no exception. Traditionally, avocado seeds can be used as a laxative medicine for kidney stones disease. Elixiris a clear and sweet hidroalkohol solution intended for oral use and a flavor is usually added to enhance the taste. This study was to determine theformula of the avocado seed elixir which has the best quality and the level of flavonoids.Elixir testing was performedusing several methods such as organoleptic, limpidity, viscosity, pH and specific weightas well as total flavonoids. The result showed that the best elixir formula was the Formula I which composed of 7%avocado seed extract, 5% ethanol, 10% propylene glycol, 40% sirupus simplex, 0.1%, essence mint and 100%aquadestilata ad. Furthermore, Elixirhad a brown color, mint aroma and pretty sweettaste. The test results showed that elixir had a viscosity of 7.92 cP; pH of 5.65; specific weight of 1.0413 g/mL andtotal flavonoids of 2.1020%.